2020
DOI: 10.1007/s13300-020-00946-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy Issues Among Adults with Type 1 Diabetes Mellitus in Saudi Arabia: A Retrospective Study

Abstract: Introduction: Type 1 diabetes mellitus (T1DM) is on the rise in Saudi Arabia. Management of T1DM is crucial in curbing the economic burden of this disease. Studies on insulin pump issues are scarce in the region. The present study aims to fill this gap. Methods: In this single-centre, retrospective study done in King Abdulaziz Medical City (KAMC) from March 2018 to March 2019, a total of 118 known Saudi T1DM adults (34 males and 84 females) were included. Data on demographics, glycated haemoglobin (HbA1c) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Data about the prevalence of air bubbles are also mentioned in two other pump surveys. 9,10 A prevalence of 16% is reported in one survey and 46% in the other. Issues with such data are that the documentation of the rate of air bubble formation/size of air bubbles depends critically on the skills of the person making the assessment.…”
Section: Publications About Air Bubblesmentioning
confidence: 90%
“…Data about the prevalence of air bubbles are also mentioned in two other pump surveys. 9,10 A prevalence of 16% is reported in one survey and 46% in the other. Issues with such data are that the documentation of the rate of air bubble formation/size of air bubbles depends critically on the skills of the person making the assessment.…”
Section: Publications About Air Bubblesmentioning
confidence: 90%
“…Reducing the risk of exercise-induced hypoglycemia can be achieved by frequent glucose monitoring and eating carbohydrates during exercise [24]. Lack of appropriate insulin pump maintenance can be manifested in several adverse events, such as pump failure, pain, adhesion, irritation, lipodystrophy, and technical issues [12,25]. It has been suggested that comprehensive patient education and frequent Blood Glucose Monitoring (SMBG or CGM) are necessary components of successful insulin pump therapy [8,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse events of insulin pump interfering with its function are still common despite the modern advances [9,10]. These include pump failure, blockage or dislocation of infusion set, infusion site infection or issues, and reduced insulin stability [11,12]. Additionally, successful insulin pump therapy is considerably influenced by adherence to self-care behaviors [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations